3D X-ray Microscopy (XRM) investigation of exogenous materials inside mussels' organs. Issue 1 (1st November 2022) - Cognigni, F; Dinarelli, S; Girasole, M; Longo, G; Fabi, G; Rossi, M
Abstract : The diffusion of pollutants in the marine environment is nowadays a well-recognized issue that is attracting growing interest from the scientific and social communities. One of the possible strategies to study the effect of pollutants is to quantify their presence inside marine organisms that are directly exposed for a certain period to the polluted environment. Among them, mussels, commonly considered as "biological water filters", stand out as ideal candidates since they are stationary animals and their food intake comes only from the filtering of the surrounding water. Thus, the evaluation of the accumulation of exogenous pollutants, in particular high-density or metallic, inside the mussel's organs and specifically in its digestive glands, is of particular interest. In this paper we characterize the accumulation of exogenous materials in digestive glands of three different mussels by means of X-ray microscopy analysis. We provide evidence of how the unique capabilities of this technique allow reconstructing a full 3D image of an entire organ and how this image can provide valuable information to identify exogenous (non-biological) pollutants. Moreover, we take full advantage from the segmentation analysis of the images by discriminating different regions of the sample according to the density. With this experimental approach we measured the sizes of the exogenous pollutants and provided evidences that they accumulate preferentiality in the low-density regions of the organ, that are richer in ducts and secretive glands.